Integration of Electrical Conductivity Concept in Measurement and Instrumentation Learning: Case Study on the Use of Soil Fertility Monitoring Tool for Electrical Engineering Students - Rahmaniar Rahmaniar; Najla Lubis; Agus Junaidi; Ihsan Fahreza (STAI Hubbulwathan Duri, 2024)
This research examines the integration of the concept of electrical conductivity in the Measurement and Instrumentation course through a soil fertility monitoring tool. Using a mixed methods approach, the study involved 30 third-year Electrical Engineering students who engaged with a specially designed soil monitoring system as a learning medium and practicum tool. Quantitative analysis showed a significant increase in student understanding, with the mean test score increasing from 42.3 (SD = 8.7) in the pre-test to 78.5 (SD = 9.5) in the post-test (p 0.001, η² = 0.61). Practical skills assessment showed that 83% of students achieved proficiency in tool calibration, while 90% successfully integrated electrical conductivity data with other parameters. Qualitative findings showed an increase in student engagement, with 92% reporting an increase in learning motivation. This implementation resulted in three main outcomes: improved theoretical understanding through hands-on experience, improved technical measurement skills, and the development of an interdisciplinary perspective linking engineering to agricultural applications. The findings suggest that integrating real-world applications into engineering education can significantly improve technical competence and practical skills, providing a model for curriculum development in other engineering disciplines. This study offers valuable insights for engineering educators who want to bridge the gap between theoretical knowledge and practical applications in measurement and instrumentation courses.